(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Hyperparathyroidism is a common finding in patients with renal insufficiency and parathyroid hormone (PTH) is considered a uremic toxin responsible for many of the abnormalities of the uremic state and bone disease. The aim of this study was to investigate the influence of permeability of low-flux versus high-flux dialysis membranes on intact PTH during hemodialysis in children. Materials and Methods. Forty-four children aged between 4 and 13 years old on regular hemodialysis were enrolled in a prospective study. Low-flux polysulfone membranes were used for at least 6 months and then the patients were switched to use high-flux polysulfone membranes for 3 months. Serum electrolytes and intact PTH before and after dialysis were compared before and after changes in dialysis membrane. Results. At the end of the 3-month use of high-flux filters, predialysis intact PTH level (49.40 ± 19.64 ng/dL) showed a highly significant decline (P < .001) compared to the predialysis intact PTH (21.67 ± 4.85 ng/dL) with low-flux membranes at the start of the study. Intact PTH level correlated negatively with serum ionized calcium and positively with serum phosphorus levels only in the predialysis samples with the use of low-flux but not high-flux filters. Conclusions. In children, high-flux dialysis membranes are more efficient in removal of intact PTH, one of the middle-sized uremic toxins, than low-flux membranes.